2-AMİNOİMİDAZOLİN'İN RATLARIN (WİSTAR) BAZI KAN PARAMETRELERİNE (A, E, C VİTAMİNLERİ VE MDA) ETKİLERİNİN ARAŞTIRILMASI - YÜKSEK, ERKAN (Fırat Üniveristesi, 2006)
[Abstract Not Available]
An investigation of the effects of 2-aminimidazoline on the levels of antioxidant vitamins (A, E and C) and MDA of rats
Keywords: Biyokimya